Nutritional, Physicochemical, and Sensorial Evaluation of Flat Bread Supplemented with Quinoa Flour - S. A. El-Sohaimy; M. G. Shehata; Taha Mehany; M. A. Zeitoun (International Journal of Food Science)
The purpose of the present research was to develop novel flat bread supplemented with quinoa flour to raise its nutritional quality and functional properties. Furthermore, evaluation of the quality of developed bread was realized with blends at 5, 10, 15, 20, 25, and 30% of quinoa flour. Chemical composition of supplemented flat bread was determined. Several properties on dough (water absorption, dough development time, stability time, elasticity, and extensibility) and their corresponding characteristics (loaf specific volume, baking loss, roundness, height, baking time, hardness, cohesiveness, springiness, resilience, gumminess, and chewiness) were then evaluated. The protein content in bread-based quinoa blends was significantly increased gradually with increasing the percentage of quinoa flour from 12.12±0.63% in control to 15.85±0.065% in 30% quinoa flour. Also, the amino acids content was increased with increasing the percentage of quinoa flour. Mineral contents in 30% quinoa flour blend such as sodium, potassium, magnesium, calcium, iron, copper, manganese, and zinc were higher than other ratios and control bread (100% wheat flour). Rheological properties of supplemented bread such as specific volume, appearance, crust and crumb texture, aroma-odor, and colour were evaluated and found to be excellent. Physicosensory characteristics of the bread fortified with quinoa flour were evaluated and the most of panelists accepted and preferred the bread supplemented with quinoa flour more than control. The obtained unique nutritional, physicochemical, and organoleptic characteristics of quinoa flour-based flat bread open a new promising prospect for utilization of quinoa flour in an industrial scale for treatment and/or prevention of malnutrition in developing counties.